Bound Morpheme Errors in Undergraduate Research Articles: The Case of an English Education Department - Faza Hannan Purinanda (JLA (Jurnal Lingua Applicata), 2023)
The graduates of English education departments are supposed to possess an advanced level of English, the knowledge of which is essential when becoming educators. Consequently, it is important to recognize prevailing grammatical errors that they commit, since teaching what is essentially flawed language use may cause damaging consequences. This study examines six undergraduate research articles from an English education department to determine common errors in the use of bound morphemes, which come into focus considering their consistent occurrences. This descriptive qualitative research describes and examines the errors in both inflectional and derivational categories. The result of the study shows that the high number of errors in bound morphemes that mark a plural noun as well as present and past tense can be attributed to the similarly high number of their uses in academic writing. Also, the grammatical issues that need to be addressed are those of non-finite verb phrases and noun phrases. A conclusion that can be drawn is that the bound morpheme errors are largely preventable. Suggestions to avoid the errors are then offered.